2011
DOI: 10.1371/journal.pone.0016971
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a High Resolution Genotyping Method for Chlamydia trachomatis Using Routine Clinical Samples

Abstract: BackgroundGenital chlamydia infection is the most commonly diagnosed sexually transmitted infection in the UK. C. trachomatis genital infections are usually caused by strains which fall into two pathovars: lymphogranuloma venereum (LGV) and the genitourinary genotypes D–K. Although these genotypes can be discriminated by outer membrane protein gene (ompA) sequencing or multi-locus sequence typing (MLST), neither protocol affords the high-resolution genotyping required for local epidemiology and accurate contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
54
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(64 citation statements)
references
References 26 publications
9
54
1
Order By: Relevance
“…Interestingly, in samples from two cats in two different catteries, where both eyes were sampled, two different genotypes were identified, which in one case differed by only one tandem repeat. These findings provide the first evidence that mixed infections with strains of different C. felis genotypes occur in cats, similar to those described for C. trachomatis in humans (39). The possibility that the different genotypes identified in these two cases may represent divergent populations resulting from instability in the MLVA loci cannot be excluded; however, analysis of two C. felis isolates passaged 10 times through chicken eggs suggests that the MLVA genotype is highly stable.…”
Section: Discussionsupporting
confidence: 63%
“…Interestingly, in samples from two cats in two different catteries, where both eyes were sampled, two different genotypes were identified, which in one case differed by only one tandem repeat. These findings provide the first evidence that mixed infections with strains of different C. felis genotypes occur in cats, similar to those described for C. trachomatis in humans (39). The possibility that the different genotypes identified in these two cases may represent divergent populations resulting from instability in the MLVA loci cannot be excluded; however, analysis of two C. felis isolates passaged 10 times through chicken eggs suggests that the MLVA genotype is highly stable.…”
Section: Discussionsupporting
confidence: 63%
“…Although high-resolution genotyping methods, such as multilocus variable number of tandem repeat analysis (MLVA), multilocus sequence typing (MLST) or microarray assay (Christerson et al, 2011;Ruettger et al, 2011;Bom et al, 2011;Wang et al 2011;Satoh et al, 2014;Hermann et al, 2015), have been recently described, their use in routine diagnostic practice is largely restricted by their complexity and high costs. So far these assays have basically played a role in epidemiological and phylogenetic analysis or in the evolutionary surveillance of specific clones, but what is really needed in the near future is the advent of rapid and cost-saving methods for faster and reliable management of patients (Pedersen et al, 2009;Xia & Xiong, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…There are now several very highly discriminating multilocus molecular typing systems, including multi locus sequence typing (MLST), for C. trachomatis that allow differentiation and subgrouping of isolates within a genotype 13 16 17 . W4–6 The multilocus variable number tandem repeat (VNTR) analysis plus analysis of the omp A gene (MLVA- omp A) high-resolution genotyping system of Pedersen et al ,13 has been successfully evaluated,18 and recent work has shown that the VNTR marker sequences are stable and therefore ideal for genotyping 19. The system consists of short, easy to amplify markers (the longest being part of the omp A gene), which are simple to manipulate and yield a high efficiency return of results as demonstrated in the quoted surveys.…”
Section: Introductionmentioning
confidence: 99%
“…The system consists of short, easy to amplify markers (the longest being part of the omp A gene), which are simple to manipulate and yield a high efficiency return of results as demonstrated in the quoted surveys. It also has an optimal ability to differentiate between genotypes,20 as measured by the Simpson's discriminatory index 13 18…”
Section: Introductionmentioning
confidence: 99%